Performance and mechanism in degradation of typical antibiotics and antibiotic resistance genes by magnetic resin-mediated UV-Fenton process - Jie Zhong (Elsevier, 2021)
Incomplete removal of antibiotics and antibiotic resistance genes (ARGs) has often been reported in wastewater treatment plants. More efficient treatment processes are needed to reduce their risks to the environment. Herein, we evaluated the degradation of antibiotics and ARGs by using magnetic anion exchange resin (MAER) as UV-Fenton catalyst. Sulfamethoxazole (SMZ), ofloxacin (OFX), and amoxicillin (AMX) were selected as the target compounds. The three antibiotics were almost completely degraded (> 99%) following the MAER UV-Fenton reaction for 30 min. From the degradation mechanism study, it was found that Fe3+/Fe2+ could be cyclically transferred from the catalyst at permeable interface, and the photo-generated electrons could be effectively separated. The dominant reactive radicals for antibiotics degradation were hydroxide during the MAER UV-Fenton reaction. The degradation pathway for sulfamethoxazole was proposed. In addition, wastewater samples from a wastewater treatment plant were applied to investigate the removal efficiency of antibiotics and their ARGs by the MAER UV-Fenton system. A rapid decrease in antibiotics and ARGs level was observed with this reaction system. The results from this study suggest that the MAER-mediated UV-Fenton reaction could be applied for the effective removal of antibiotics and ARGs in wastewater.